Levosimendan protects against ischemia – reperfusion injury in the human heart muscle. A pilot study - Kunecki Marcin; Oleksy Tomasz; Nozynski Jerzy; Podolec Piotr; Biernat Jolanta; Deja Marek Andrzej; Golba Krzysztof Stanislaw; Plazak Wojciech (Current Issues in Pharmacy and Medical Sciences, 2022)
The consequences of myocardial infarction (MI) are an increasing problem worldwide. Despite spectacular progress in the invasive treatment of ischemic heart disease, the ability to limit the ischemia-reperfusion (I/R) injury remains largely unrealized. Recent studies have shown that stimulation of opioid receptors may confer a cardioprotective effect against I/R injury. Levosimendan, the inodilator, is indicated for the short-term treatment of acutely decompensated heart failure. We tested the hypothesis that levosimendan may provide cardioprotection in the opioid-like mechanism in the human myocardium.